Tunneling and Company Performance in The Financial Industry In Indonesia - Supatmi Supatmi; Kristina Devihanna Batubara (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
This study aims to find empirical evidence of the impact of related party transactions, particularly tunneling transactions, on the performance of the Indonesian financial industry. The research samples were 105 companies that are members of the financial industry listed on the Indonesia Stock Exchange (IDX) during 2018-2020 with a total of 300 observations. Tunneling was measured using the proportion of related party transactions related to trade receivables, other receivables, and assets other than trade receivables. Company performance was measured by accounting performance as proxied by return on assets (ROA) and market performance as proxied by Tobin’s Q. The results showed that the more financial companies tunneling through related party transactions related to assets other than trade receivables, the lower the accounting performance (ROA) but the higher the market performance. Meanwhile, tunneling through related party transactions of trade and other receivables in the financial industry was shown to have no effect on accounting or market performance.